The Tabu Search approach in coherent co-synthesis of multiprocessors systems - Drabowski, Mieczysław (Studia Informatica. System and information technology, 2006)
This paper presents the use of Tabu Search algorithm for solving the problems of coherent synthesis of multiprocessor computer systems. The paper includes a coherent solution of both optimization of partition resources and optimization of tasks scheduling. This publication shows results of computational experiments for different instances of system synthesis problems.